Unveiling The Diagnosis Pitfall: Complete Heart Block Presenting In Acute Coronary Syndromes Without Chest Pain And Non-Ischemic Electrocardiography In A Young Adult - Suprayoga, Imam Mi'raj; Rizal, Ardian; Widito, Sasmojo; Rahimah, Anna Fuji (Heart Science Journal, 2023)
Background: The majority of studies indicate that the asymptomatic or atypical presentation of acute coronary syndrome (ACS) as a significant manifestation of coronary artery disease (CAD) is associated with a poor prognosis.Objective: The purpose of this study was to characterize the clinical characteristics and management of ACS patients who presented without chest pain and non-ischemic electrocardiogram (ECG).Case presentation: A 31 years old man with syncope was brought to our hospital. ECG revealed total AV block (TAVB) without ST segment changes. First, he was diagnosed with cardiac syncope because his ECG showed no ischemic sign. He had a strong familial history of CAD, so we examined his cardiac enzymes and found an increase in serial cardiac enzymes. Then, he was diagnosed with non-ST elevation myocardial infarction (NSTEMI). Early invasive strategy with chronic total occlusion (CTO) at osteal right coronary artery (RCA) and acute total occlusion at mid RCA with implantation of 1 DES at osteal-proximal RCA was selected for this patient. After five days of hospitalization, he discharged home with medicines. Conclusion: In order to significantly lower their morbidity and mortality, this group of high-risk patients needs to receive improved early diagnostic and treatment choices.